2020
DOI: 10.3844/ajbbsp.2020.9.14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Impact Of TLR9 Antagonist ODN 2088 Against Carbon Tetrachloride (CCl4)-Induced Hepatic Injury

Abstract: The main objective of this study is to evaluate the hepatoprotective impact of TLR9 antagonist ODN 2088 against carbon tetrachloride (CCl 4)-induced acute liver injury. In this study, 24 mice were grouped into four groups. CCl 4 was introduced in all groups except for the control group intraperitoneally after pretreatment with ODN 2088 and silymarin for seven days. To assess the liver injury, serum alanine Aminotransferase (ALT) and aspartate Aminotransferase (AST) were estimated and histopathological changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…All these findings indicate that targeting TLRs could mitigate the clinical presentation, outcomes, and prognosis of COVID-19. ODN2088 is a murine TLR9 antagonist that has been shown to be potent in preventing hepatic inflammation and fibrosis in a CCl4-induced liver fibrosis mouse model [ 23 , 33 ]. In this study, we evaluated ODN2088 as a potential therapeutic agent for prevention of pulmonary injury, inflammation, and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these findings indicate that targeting TLRs could mitigate the clinical presentation, outcomes, and prognosis of COVID-19. ODN2088 is a murine TLR9 antagonist that has been shown to be potent in preventing hepatic inflammation and fibrosis in a CCl4-induced liver fibrosis mouse model [ 23 , 33 ]. In this study, we evaluated ODN2088 as a potential therapeutic agent for prevention of pulmonary injury, inflammation, and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotide ODN2088 (a DNA sequence) inhibits the activity of TLR9 and its downstream signaling effectors by disturbing the co-localization of unmethylated CpG di-nucleotides with TLR9 [ 22 ]. A previous study showed that ODN2088 inhibits the liver inflammation and fibrosis induced by CCl4 [ 23 ]. In the present study, a bleomycin-induced lung injury mouse model was used to evaluate the impact of TLR9 inhibition by ODN2088 on the lung damage, inflammation, and fibrosis commonly seen in ARDS in COVID-19 patients.…”
mentioning
confidence: 99%